ڕۆڵى سیاسى و دادوەرى و سەربازى مزگەوتەکان لە شارستانیەتی ئیسلامی هـەرێمى جەزیرە بەنمونە لە سەدەى (١ـ٧ک/٧ـ١٣ز) - الدین, پ.د عطا عبدالرحمن محی; محمد, شیرین صابر (Sulaimani Journal for Humanities, 2023)
The mosque as a religious institution played an important role in the Islamic community, not only as a place of worship but also as a center for political and military activities. Jazira province as part of the Islamic state, the mosques in the cities of this region were similar to other mosques in the Islamic world, in addition to their religious role, they participated directly in the political and military situation of the cities. Or it was known as the House of Emirate, and through the rituals of prayer on Friday, the name of the caliph and the princes was mentioned above the pulpits and called for concern, and the mosques were used as a house of justice, and the preachers in the mosques supported the Islamic army and encouraged Muslims to participate in the fight against the enemies of the Islamic state.
Keywords: مزگەوت ئیسلام هـەرێمى جەزیرە خانەى میر دادوەرى وتاربێژ